CINDERELLA - Fandel, Jennifer; Simpson, Michelle (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2021)
"The bright lights and fancy parties are calling--but Cinderella's stepmother won't let her go. A sprinkle of magic from a fairy godmother, and Cinderella is on her way in a party dress! Will she connect with the prince, or be stuck with her family forever?"--
Graphic novel adaptation of: Cinderella
Keywords: Cinderella -- (Legendary character) -- Comic books, strips, etc; Prince -- Comic books, strips, etc